Agricultural Insurance : principles and organization and application to developing countries - Ray, Parimalkumar K. (Oxford ; New York : Pergamon Press, 1967)
The present volume is an attempt to marry the principles and organization of the major systems of farm insurance in the developed countries, particularly in the United Kingdom and the United States, and to some extent also in Canada and western Europe, with the adaptation and application of these principles to the most urgent need of, and the situations in the developing countries.
Includes index.
Includes bibliographical references: p. 309-313.
ne 14/05/2918
Loan
Keywords: Agricultural insurance